Fine needle aspiration biopsy proves increased T-lymphocyte proliferation in tumor and decreased metastatic infiltration after treatment with doxorubicin bound to PHPMA copolymer carrier. (26th April 2013) - Betka, Jaroslav; Hovorka, Ondrej; Boucek, Jan; Ulbrich, Karel; Etrych, Tomas; Rihova, Blanka
Abstract: Introduction : Fine needle aspiration biopsy (FNAB) is an easy method with an option of repetitive withdrawal of cell material. Methods : First, mice were inoculated with mouse T-lymphoma, after 10 d the samples from tumor, lymph nodes and spleen gained by FNAB and excision were analyzed by flow cytometry. Tumor progression was compared to the control group simultaneously. Then, 10 d after tumor cell inoculation free doxorubicin (DOX) or different PHPMA DOX conjugates were injected. Cell material was analyzed to detect subpopulations of lymphocyte infiltrate, and levels of cytokines in correlation with progression or regression of the disease. Results : FNAB has no influence on the tumor's growth or survival of experimental animals. After treatment with PHPMA conjugates there was a significant increase of T-lymphocyte subpopulations in tumor microenvironment compared to controls or free DOX, but only in mice with confirmed macroscopic regression of tumor within two weeks. Mice treated with conjugates showed significantly lower cancer infiltration of lymph nodes and spleen. Conclusion : FNAB provides a great benefit to in vivo monitoring of cell changes directly in the tumor after treatment. The number of infiltrating T-lymphocytes increases in correlation with consecutive tumor eradication after treatment with PHPMA. This proves that not only direct cytotoxic but also imunostimulating effect are necessary for successful treatment.